Implementasi Latihan Sepak Sila Berpasangan Terhadap Peningkatan Hasil Belajar Pada Permainan Sepak Takraw - Pribadi, Imam; Kahar, Irsan; Hakim, Nurwahidin; Tombeu, Oskar (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
The purpose of this study was to find out that the implementation of the practice of silat in pairs can improve learning outcomes in the game of sepak takraw for the students of SDN 30 Mattiro Walie Class Va.. Data collection techniques applied in this study were teacher activity observations and student activity observation sheets and student skill tests. This research was conducted in 2 cycles and student evaluation tests were conducted at the end of each cycle. The results of the percentage of observation of student activities in cycle 1 are the completeness of student learning outcomes in each cycle on average 50.3% from the cognitive aspect, 48.3% affective aspects and 56.8% psychomotor aspects. in cycle I. And Cycle II Completeness Completeness of student learning outcomes in each cycle is averaged from the Cognitive aspect 80.1%, Affective aspect 92.0% and Psychomotor aspect 96.0%. The results of this study stated that the application of the practice of cross-syllabus in pairs can improve the learning outcomes of sepak takraw and can improve the quality and foster joy, motivate students in learning.